Worldwide variations in COVID-19 vaccination policies and practices in liver transplant settings: results of a multi-society global survey - Di Maira, Tommaso; Vinaixa, Carmen; Izzy, Manhal; Paolo Russo, Francesco; Kirchner, Varvara A.; Rammohan, Ashwin; Belli, Luca Saverio; Polak, Wojciech Grzegorz; Berg, Thomas; Berenguer, Marina (Frontiers in Transplantation, 2024)
Background: Despite the WHO's report of 24 available SARS-CoV-2 vaccines, limited data exists on vaccination policies for liver transplant (LT). To address this, we conducted a global multi-society survey (EASL-ESOT-ELITA-ILTS) in LT centers.Methods: A digital questionnaire assessing vaccine policies, safety, efficacy and center data was administered online to LT centers.Results: Out of 168 responding centers, 46.4%, 28%, 13.1%, 10.7% and 1.8% were from European, American, Western Pacific, Southeast Asia and Eastern Mediterranean Regions.Most LT centers prioritized COVID-19 vaccine access for LT patients (76%) and healthcare workers (86%), while other categories had lower priority (30%).One-third of responders recommended mRNA vaccine exclusively, while booster doses were widely recommended (81%).One-third conducted post-vaccine liver function tests post COVID-19 vaccine. Only 16% of centers modified immunosuppression, and mycophenolate discontinuation or modification was the main approach.The side effects rate was 1 in 1000 vaccinated patients, with thromboembolism, acute rejection, and allergic reaction being the most severe. mRNA showed fewer side effects (-3.1, p=0.002).: COVID-19 vaccines and booster doses were widely used among LT recipients and healthcare workers, without a specific vaccine preference. Preventative immunosuppression adjustment post-vaccination was uncommon. mRNA vaccines demonstrated a favorable safety profile in this population.